Valsalva manoeuver, intra‐ocular pressure, cerebrospinal fluid pressure, optic disc topography: Beijing intracranial and intra‐ocular pressure study. (11th September 2013) - Zhang, Zheng; Wang, Xiaolei; Jonas, Jost B.; Wang, Huaizhou; Zhang, Xiaojun; Peng, Xiaoxia; Ritch, Robert; Tian, Guohong; Yang, Diya; Li, Lei; Li, Junfa; Wang, Ningli
Abstract Purpose To assess whether a Valsalva manoeuver influences intra‐ocular pressure (IOP), cerebrospinal fluid pressure (CSF‐P) and, by a change in the trans‐laminar cribrosa pressure difference, optic nerve head morphology. Methods In the first part of the study, 20 neurological patients (study group 'A') underwent measurement of IOP and lumbar CSF‐P measurement in a lying position before and during a Valsalva manoeuver. In the second study part, 20 healthy subjects (study group 'B') underwent ocular tonometry and confocal scanning laser tomography of the optic nerve head before and during a Valsalva manoeuver. Results During the Valsalva manoeuver in study group 'A', the increase in CSF‐P by 10.5 ± 2.7 mmHg was significantly (p < 0.001) higher than the increase in IOP by 1.9 ± 2.4 mmHg. The change in CSF‐P was not significantly (p = 0.61) correlated with the change in IOP. During the Valsalva manoeuver in study group 'B', IOP increased by 4.5 ± 4.2 mmHg and optic cup volume (p < 0.001), cup/disc area ratio (p = 0.02), cup/disc diameter ratio (p = 0.03) and maximum optic cup depth (p = 0.01) significantly decreased, while neuroretinal rim volume (p = 0.005) and mean retinal nerve fibre layer thickness (p = 0.02) significantly increased. Conclusions The Valsalva manoeuver‐associated short‐term increase in CSF‐P was significantly larger than a simultaneous short‐term increase in IOP. It led to a Valsalva manoeuver‐associated decrease or reversal of the trans‐laminar cribrosa pressure difference, which was associated with a change in the three‐dimensional optic nerve head morphology: optic cup‐related parameters decreased and neuroretinal rim‐related parameters enlarged. These findings may be of interest for the pathogenesis of glaucomatous optic neuropathy.